148k views
10 votes
____ Al(NO3)3 + ____ FeCl2 --> _____ Fe(NO3)2 + ______AlCl3

~
how to fix/ balance this chemical reaction?

User Mycoola
by
5.5k points

1 Answer

5 votes

The balanced equation

2Al(NO₃)₃ + 3FeCl₂ ⇒ 3Fe(NO₃)₂ + 2AlCl₃

Further explanation

Given

Reaction

Al(NO₃)₃ + FeCl₂ --> Fe(NO₃)₂ + AlCl₃

Required

Balanced equation

Solution

Give a coefficient

aAl(NO₃)₃ + bFeCl₂ --> Fe(NO₃)₂ + cAlCl₃

Make an equation

Fe, left=b, right=1⇒b=1

N, left=3a, right=2⇒3a=2⇒a=2/3

Cl, left=2b, right=3c⇒2b=3c⇒2.1=3c⇒c=2/3

The equation becomes :

2/3Al(NO₃)₃ + FeCl₂ --> Fe(NO₃)₂ + 2/3AlCl₃ x3

2Al(NO₃)₃ + 3FeCl₂ --> 3Fe(NO₃)₂ + 2AlCl₃

User Avinash Shah
by
5.5k points